2006
DOI: 10.1016/j.profnurs.2006.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Education/Community Collaborations for Undergraduate Nursing Gerontological Clinical Experiences

Abstract: Abstract:In 2000, the American Association of Colleges of Nursing and the John A. Hartford Foundation Institute for Geriatric Nursing developed guidelines to help nurse educators incorporate gerontological nursing content into baccalaureate curricula. In 2001, the Hartford Foundation also provided grant monies to nursing programs to support gerontology curricular innovations and new clinical experiences. The funding allowed faculty to focus time, energy, and resources on gerontological nursing education. We, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 8 publications
1
20
0
Order By: Relevance
“…The characteristics of the enriched environments experienced by these students comprise security, purpose, achievement and significance in learning to care proficiently for older people and belonging to the community of the workplace. The findings support other studies on clinical placements in RAC in The United Kingdom, Norway and Australia (Barba and Gendler 2006; Robinson et al. 2008; Berntsen and Bjork 2010).…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…The characteristics of the enriched environments experienced by these students comprise security, purpose, achievement and significance in learning to care proficiently for older people and belonging to the community of the workplace. The findings support other studies on clinical placements in RAC in The United Kingdom, Norway and Australia (Barba and Gendler 2006; Robinson et al. 2008; Berntsen and Bjork 2010).…”
Section: Introductionsupporting
confidence: 90%
“…There is general agreement that clinical placements in undergraduate programs should reflect the broader‐spectrum nature of the care of older people in healthcare settings (Barba and Gendler 2006; Chen et al. 2007).…”
mentioning
confidence: 99%
“…Current recommendations state that nursing curricula should contain both a required gerontological course with theoretical (also referred to as lecture content) and clinical practice components, and gerontological content threaded throughout the curriculum (American Association of Colleges of Nursing 2000). This proves challenging, however, for a variety of reasons, including the growing popularity of accelerated programmes and the common perception that curricula are already overflowing, creating the argument that there is simply no time for more gerontological nursing content (Barba & Gendler 2006, Deschodt et al. 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A literature search for research published in English between 2000–2010 revealed that most of the research focusing on gerontological education have been American studies detailing the successes and challenges of incorporating gerontological content into curricula (Aud et al. 2006, Barba & Gendler 2006, Blais et al. 2006, Burbank et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation